Photo-thermal catalysis for sustainable energy production and environmental treatment - Darko, Daniel Amoako; Sahu, Sangeeta; Rathore, Jyoti; Kaur, Lakhvinder; Jain, Bhawana; Kanungo, Shweta; Rawat, Reena (Frontiers in Energy Research, 2024)
Photo-thermal-catalysts (PTC) exceptional features and ability to concurrently solve sustainable energy requirements and environmental problems have drawn scientific interest.The photo-thermal effect is the process by which photo-thermal conversion materials transform radiant energy from light into thermal energy. The photo-thermal therapy of energy and environmental treatment faces the urgent task of developing effective photo-thermal agents to address complicated problem demands. In this study, we take a look at the fundamental principles and underlying process of photo-thermal material catalysis. In addition, this review provides a concise summary of the most up-to-date findings concerning photo-thermal catalysis materials, which have been aggressively researched for a wide-spread sustainable energy and environment treatment uses. In order to motivate the creation of a high-efficiency photothermal catalytic pathway, the criteria and techniques for designing photo-thermal catalysts are presented. This will make it possible for a better absorption of the whole spectrum of solar energy as well as a greater conversion of solar energy to heat. Theoretical direction is offered for the continued development of this technology, and the promise of the practical use of photothermal catalysis for different solar-driven interfacial photo-thermal conversion technologies is anticipated. This paper offers a unique perspective on photo-thermal catalysis focussing on the synergistic effects and suggesting a potential route for future applications.